Baricitinib in patients with moderate‐to‐severe atopic dermatitis and inadequate response to topical corticosteroids: results from two randomized monotherapy phase III trials. (1st August 2020) - Simpson, E.L.; Lacour, J.‐P.; Spelman, L.; Galimberti, R.; Eichenfield, L.F.; Bissonnette, R.; King, B.A.; Thyssen, J.P.; Silverberg, J.I.; Bieber, T.; Kabashima, K.; Tsunemi, Y.; et al.
Summary: Background: Baricitinib, an oral selective Janus kinase 1 and 2 inhibitor, effectively reduced atopic dermatitis (AD) severity in a phase II study with concomitant topical corticosteroids. Objectives: To evaluate the efficacy and safety of baricitinib in patients with moderate‐to‐severe AD who had an inadequate response to topical therapies. Methods: In two independent, multicentre, double‐blind, phase III monotherapy trials, BREEZE‐AD1 and BREEZE‐AD2, adults with moderate‐to‐severe AD were randomized 2 : 1 : 1 : 1 to once‐daily placebo, baricitinib 1 mg, 2 mg, or 4 mg for 16 weeks. Results: At week 16, more patients achieved the primary end point of Validated Investigator's Global Assessment of AD (0, 1) on baricitinib 4 mg and 2 mg compared with placebo in BREEZE‐AD1 [ N = 624; baricitinib 4 mg 16·8% ( P < 0·001), 2 mg 11·4% ( P < 0·05), 1 mg 11·8% ( P < 0·05), placebo 4·8%], and BREEZE‐AD2 [ N = 615; baricitinib 4 mg 13·8% ( P = 0·001), 2 mg 10·6% ( P < 0·05), 1 mg 8·8% ( P = 0·085), placebo 4·5%]. Improvement in itch was achieved as early as week 1 for 4 mg and week 2 for 2 mg. Improvements in night‐time awakenings, skin pain and quality‐of‐life measures were observed by week 1 for both 4 mg and 2 mg ( P ≤ 0·05, all comparisons). The most common adverse events in patients treated with baricitinib were nasopharyngitis and headache. No cardiovascular events, venous thromboembolism, gastrointestinal perforation, significant haematological changes, or death were observed with any baricitinib dosage. Conclusions: Baricitinib improved clinical signs and symptoms in patients with moderate‐to‐severe AD within 16 weeks of treatment and induced rapid reduction of itch. The safety profile remained consistent with prior findings from baricitinib clinical development in AD, with no new safety concerns. Linked Comment: Drucker. Br J Dermatol 2020; 183:199–200 .